Decentralised and Centralised Fixed Structure H ∞ Robust Loop Shaping for the MIMO Microsurgical Manipulation Based on PSOGSA - Somyot Kaitwanidvilai; Poom Konghuayrob; H. Aoyama (IET Control Theory and Applications, 2026)
ABSTRACT This paper presents decentralised and centralised fixed‐structure H∞ robust control methods optimised by the Particle Swarm Optimisation and Gravitational Search Algorithm (PSOGSA) for a coupled multi‐input multi‐output (MIMO) microsurgical manipulator. The design framework explicitly considers uncertainties and disturbance constraints. Conventional H∞ loop‐shaping controllers are typically of high order, complex, and difficult to implement in practice. To address this limitation, Proportional‐Integral‐Derivative (PID)‐structured decentralised and centralised H∞ controllers are proposed, providing compact structures while retaining robustness. The novelty of this work lies in embedding H∞ robustness criteria into practical PID‐based frameworks, bridging the gap between theoretical robust design and experimental implementation in microsurgical applications. The proposed controllers are evaluated against a reduced‐order H∞ controller derived from Hankel norm approximation and a Ziegler–Nichols tuned PID controller, using both simulation and experimental studies. Results demonstrate that the proposed controllers achieve improved stability margins (0.449–0.521 compared with 0.436 for the reduced‐order design), maintain low root‐mean‐square errors (≈0.067–0.089) and remain robust under voltage disturbances where conventional PID control fails. These findings confirm the contribution of a practical and efficient robust control strategy for enhancing the precision and reliability of microsurgical manipulators.
Keywords: Piezoelectric Actuators and Control; Soft Robotics and Applications; Robotic Mechanisms and Dynamics